« Vols, force et mort d’hommes ». La violence seigneuriale dans le royaume de Castille à la fin du Moyen Âge - Hipólito Rafael Oliva Herrer (Criminocorpus)
The aim of this article is to analyse both the forms of noble violence against rural communities in Castile during the XIVth and XVth centuries and the discourse used to denounce them. From this point of view, the article shows the continuity, during the period, of practices of seigniorial violence more pronounced in moments of open political conflict throughout the kingdom. This kind of violence cannot be only reduced to the expression of a noble identity and reveals an expansionist seigniorial logic. Beside, the proliferation of complaints about seigniorial violence shows the progress of a framework which permits to define these usual practices as violent, and therefore, illegitimate, and permits to articulate resistances.